The graph in the question is missing.
Answer:
y = 
Step-by-step explanation:
The function is cubic
It has roots as -4, -4 , 6
this means the value of x = -4, -4 , 6 which makes the entire equation zero
so we have solutions as
x+4 = 0
x+4 = 0
x- 6 = 0
on forming a cubic equation using these
(x+4)(x+4)(x-6)
the equation passes through (2,36)
put x = 2
(2+4)(2+4)(2-6) = (6)*(6)*(-4)
which exceeds 36 so we product the equation with -1/4 to get 36
Final equation
y = 
y = 
4x plus 4y seems to be equal to that situation right there
Answer: 16p^8q^4r^8 The yellow one
Step-by-step explanation:
Step 1: Use Multiplication Distributive Property: (xy)^a = x^a y^a. So 4^2p^2(q^3)(r^4)^2
Step 2: Simplify 4^2 to 16. So 16p^2(q^3)^2(r^4)^2
Step 3: Use Power Rule: (x^a)^b=x^ab. So 16p^2q^6(r^4)^2
Step 4: Use Power Rule: (x^a)^b=x^ab. So the answer is 16p^2q^6r^8. The yellow one
Answer:
13x-4
Step-by-step explanation:
Answer:
I would say...
C.)x - 5 = 3 (x + 2)
Really really sorry if I'm wrong...
One thing I can say is that when it says 5 less than a #, that means the # is being subtracted from another #...